CORRELATION BETWEEN DENGUE INCIDENCES AND POPULATION OF A. aegypti AND A. albopictus - SINGH, DEEPTI; MAHESHWARI, GIRISH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
This research aim to determine the correlation between dengue incidence and population dynamics of dengue vector ( A. aegypti and A. albopictus ) to explore the possibilities of using our findings to improve control of dengue. The most effective way to characterize the dengue risk - vector population association was to carry out prospective monthly field survey, i.e. mosquito density, dengue incidences and severity of diseases. The study design was limited to reported cases in Agra region only. Data of dengue cases collected from various hospitals where techniques for actively identifying diseases were available. To determine the correlation between dengue incidences and population of Aedes mosquitoes, Pearson’s Correlation Analysis was performed with the help of SPSS software. The value of Pearson's Correlation R = 0.091 with high level of significance that is P = 0.779. A low Pearson’s Correlation indicates a biological relationship between dengue incidence and population variation of Aedes species. It also shows that there are other factors also those influence the process. Similarly, the incidences of dengue were also highly related to the presence of A. albopictus. In this case the value of R = 0.685 and P = 0.014 which is also highly valuable. Results from study stated that the presence of Aedes aegypti was linearly related to incidences of dengue cases.